2018
DOI: 10.1186/s12936-018-2264-y
|View full text |Cite
|
Sign up to set email alerts
|

Humanized DRAGA mice immunized with Plasmodium falciparum sporozoites and chloroquine elicit protective pre-erythrocytic immunity

Abstract: BackgroundHuman-immune-system humanized mouse models can bridge the gap between humans and conventional mice for testing human vaccines. The HLA-expressing humanized DRAGA (HLA-A2.HLA-DR4.Rag1KO.IL2RγcKO.NOD) mice reconstitute a functional human-immune-system and sustain the complete life cycle of Plasmodium falciparum. Herein, the DRAGA mice were investigated for immune responses following immunization with live P. falciparum sporozoites under chloroquine chemoprophylaxis (CPS-CQ), an immunization approach th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 43 publications
(76 reference statements)
0
30
0
Order By: Relevance
“…DRAGA mice express HLA-A2.1 and HLA-DR0401 molecules on a Rag1KO.IL2RγcKO.NOD (NRG) background, and they have been described previously [52][53][54][55] . HLA-A2.…”
Section: His-reconstitution Of Draga Micementioning
confidence: 99%
See 1 more Smart Citation
“…DRAGA mice express HLA-A2.1 and HLA-DR0401 molecules on a Rag1KO.IL2RγcKO.NOD (NRG) background, and they have been described previously [52][53][54][55] . HLA-A2.…”
Section: His-reconstitution Of Draga Micementioning
confidence: 99%
“…Technologies, Vancouver, BC, Canada) containing approximately 10 5 human HSC (CD34 + ) as measured by FACS using a mouse anti-human CD34 antibody (BD Biosciences, San Jose, CA, USA) as described [49][50][51][52][53][54] . The procedures for assessing human T and B cell reconstitution in peripheral blood by FACS have been described [49][50][51][52]72 . As documented in our previous studies, >90% of DRAGA mice are fully reconstituted.…”
Section: His-reconstitution Of Draga Micementioning
confidence: 99%
“…With respect to T cell responses, this work has largely been limited to either HLA transgenic humanized mice that universally express HLA-A*02 or to the BLT humanized mice used in this study. These studies have demonstrated the ability to induce T cell responses following infection with live or inactivated microbes (43,44,114) or through delivery of protein or peptide antigens (115,116). Here, we build on these results by demonstrating that the engrafted human immune system in BLT mice is also responsive to immunization that can accelerate the development of functional antigen-specific responses able to mediate control of HIV-1.…”
Section: Figmentioning
confidence: 87%
“…To date, a number of studies have demonstrated with varying success the ability to immunize different humanized mouse models and induce humoral and cellular immunity (30,43,44,(110)(111)(112)(113)(114)(115)(116). With respect to T cell responses, this work has largely been limited to either HLA transgenic humanized mice that universally express HLA-A*02 or to the BLT humanized mice used in this study.…”
Section: Figmentioning
confidence: 99%
“…Earlier generations of human immune system humanized mice showed poor ability to support reconstitution and development of functional human T cells or B cells that are able to secrete IgG ( 17 ). With the introduction of HLA transgenes in the Rag1KO.IL2RγcKO.NOD (NRG) background, the DRAG mice (HLA-DR4.Rag1KO.IL2RγcKO.NOD), and DRAGA mice (HLA-A2.HLA-DR4.Rag1KO.IL2RγcKO.NOD) infused with HLA-matched human hematopoietic stem cells (HSC) have been shown to repopulate the mouse thymus and to reconstitute functional human T cells that support human B cell immunoglobulin class switching and secretion of human IgG ( 18 24 ). These mice have been used successfully for supporting infection with human pathogens, such as Plasmodium falciparum (malaria), HIV, Zika, and influenza A virus, and for analyzing human immune responses upon infection or vaccination ( 20 25 ).…”
Section: Introductionmentioning
confidence: 99%